TRANSFORMATION OF CORRESPONDENCE LEARNING WITH GOOGLE SITES INTERACTIVE MEDIA IN PUBLIC VOCATIONAL SCHOOLS - Nurmalahayati, Anissa; Faslah, Roni; Wolor, Christian Wiradendi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This research was conducted with the aim of determining the level of feasibility and practicality of Google Sites-based interactive learning media on transmission material at Public Vocational School 1 Bogor. This research uses the Research and Development (RnD) method with the development of the ADDIE (Analysis, Design, Implementation, Evaluation) model. The research subjects consisted of 2 material experts, 2 language experts, 2 media experts and 107 class XI Office Management and Business Services (MPLB) students. The data collection technique uses a questionnaire with a 1-5 Likert scale. Data analysis techniques were carried out using expert validation tests and practicality tests. The results of the research and development that has been carried out show that Google Sites-Based Interactive Learning Media for Class XI Correspondence Material at Public Vocational School 1 Bogor is declared feasible and very practical and can be used in learning activities.